Expansion of CD8+ T cells that express low levels of the B cell-specific molecule CD20 in patients with multiple myeloma - Katopodis, O.; Liossis, S.-N.; Viglis, V.; Pouli, A.; Dimopoulos, M.-A.; Sfikakis, P.P. (British Journal of Haematology, 2003)
An expanded cytotoxic/memory T-cell subpopulation expressing low levels of the B-cell-specific CD20 molecule was found in peripheral blood and bone marrow of patients with multiple myeloma at the time of diagnosis, but returned to normal levels following treatment. CD3+CD20dim cells were also increased in monoclonal gammopathy of unknown significance albeit at lower levels. Lower CD3+CD20dim cell numbers at baseline may be associated with lack of response to treatment and a poor outcome. Because expansion of these T cells may be related to disease status, further studies should investigate their potentially unique function in plasma cell dyscrasias.
Keywords: CD20; Monoclonal gammopathy of unknown significance; multiple myeloma; T-cell immunophenotype